2013
DOI: 10.1038/mp.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hippocampal volume and increased anxiety in a transgenic mouse model expressing the human CYP2C19 gene

Abstract: Selective serotonin reuptake inhibitors, tricyclic antidepressants, various psychoactive drugs, as well as endogenous steroids and cannabinoid-like compounds are metabolized by the polymorphic cytochrome P450 2C19 (CYP2C19). Absence of this enzyme has been recently shown to associate with lower levels of depressive symptoms in human subjects. To investigate endogenous functions of CYP2C19 and its potential role in brain function, we have used a transgenic mouse model carrying the human CYP2C19 gene. Here, CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 67 publications
7
49
0
Order By: Relevance
“…Most interestingly in this context is a study recently published by Persson and colleagues (Persson et al 2014), demonstrating hippocampal atrophy and depressive-like symptoms in a mouse model expressing the human CYP2C19 gene. Although a precise mechanism is not revealed, the authors indeed suggest (yet to be identified) ''endogenous substrates'' of overexpressed CYP2C19 to mediate the observed effects (Persson et al 2014). Most interestingly, however, CYP2C19 is also an isozyme involved in the metabolism of endogenous RA (McSorley and Daly 2000).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Most interestingly in this context is a study recently published by Persson and colleagues (Persson et al 2014), demonstrating hippocampal atrophy and depressive-like symptoms in a mouse model expressing the human CYP2C19 gene. Although a precise mechanism is not revealed, the authors indeed suggest (yet to be identified) ''endogenous substrates'' of overexpressed CYP2C19 to mediate the observed effects (Persson et al 2014). Most interestingly, however, CYP2C19 is also an isozyme involved in the metabolism of endogenous RA (McSorley and Daly 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, functionally relevant polymorphisms of RA-degrading CYP450 isozymes have recently been linked with major depression and response to antidepressant treatment (Sim et al 2010;Ruano et al 2011). Most interestingly in this context is a study recently published by Persson and colleagues (Persson et al 2014), demonstrating hippocampal atrophy and depressive-like symptoms in a mouse model expressing the human CYP2C19 gene. Although a precise mechanism is not revealed, the authors indeed suggest (yet to be identified) ''endogenous substrates'' of overexpressed CYP2C19 to mediate the observed effects (Persson et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Highlighting the clinical impact of the CYP450-system in the context of MDD, an association has been found between functionally relevant polymorphisms of RA-catabolizing CYP450-isozymes, such as CYP2C19, on the one hand, and response to antidepressant treatment 26 as well as prevalence of depressive symptoms and risk for depression and suicide itself on the other hand 27,28 . Consequently, transgenic mice expressing the mutant human CYP2C19 gene were found to exhibit hippocampal atrophy and depressive-like symptoms 29 . Against the background of RA´s involvement in MDD pathogenesis and its catabolism via CYP450-isozymes, RA signaling might represent a missing link between pathologically increased catabolism (e.g.…”
Section: Ra Signaling In Mddmentioning
confidence: 99%
“…CYP2C19 expression has been recently shown in the human fetal brain. 21 It also participates in the metabolism of endogenous steroids and cannabinoid-like compounds, 20 which might collectively underlie the observed alterations in brain development and affective behavior observed in a transgenic mouse model carrying the human CYP2C19. 21 Consistently, individuals who do not produce active CYP2C19 protein because they are homozygous for the null protein activity allele *2 selfreported lower levels of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…21 It also participates in the metabolism of endogenous steroids and cannabinoid-like compounds, 20 which might collectively underlie the observed alterations in brain development and affective behavior observed in a transgenic mouse model carrying the human CYP2C19. 21 Consistently, individuals who do not produce active CYP2C19 protein because they are homozygous for the null protein activity allele *2 selfreported lower levels of depressive symptoms. 22 In order to evaluate the combined influence of these two highly polymorphic genes involved in the metabolism of CNS drugs and substances, a helpful strategy might be based on calculating a 'drug metabolic capacity score', which we propose.…”
Section: Introductionmentioning
confidence: 99%